A Bhagavad Gita‐inspired Linked Leadership Model. Issue 3 (1st December 2021) - Simpson, Ace V.; Pina e Cunha, Miguel
Abstract : India's Bhagavad Gita is a Sanskrit text that is increasingly being explored for leadership and management wisdom. We take a literal approach to engaging with the entirety of the Gita 's 700 verses across its 18 chapters as a coherent whole and integrating the lessons into a linked leadership model. The model provides a flexible framework highlighting topics recognized as relevant to leadership, including self‐leadership, integrity, virtue, servant leadership, motivation, team dynamics, culture, ecology, meaning, and purpose.